Opowieściowy wzór przeznaczenia bohaterów - Čechová, Mariana (Slavia Occidentalis, 2017)
As a result of an analysis of folk types 461 and 930 (‘protected by fate’) their thematic and motif-based intersections in the comparative framework of European and Asian literary tradition can be identified. At the same time, these intersections are inter-culturally valid. The research shows that an invariant semanteme of all the myths, folk tales and legends studied is the unsuccessful attempt of a man of high social standing and power to kill his successor, who has been chosen by fate. This ancient narrative motif also contains the famous Biblical motifs, such as the persecution of a child, heavenly omens and the fulfilment of a prophecy.